Momentary Affect, Stress Coping, and Food Intake in Mother-Child Dyads - Mason, Tyler B. (Health Psychol, 2019)
BACKGROUND. Momentary affect and stress in mothers and their children may be an important predictor of food intake in the natural environment. This study hypothesized that there would be parallel actor and partner effects such that mothers’ and children’s negative affect (NA), positive affect (PA), and ability to cope with stress would be associated with their own and the other dyad member’s unhealthy and healthy food intake in a similar pattern. METHODS. Participants included 202 mother-child dyads (child age range=8–12) who responded to randomly prompted ecological momentary assessment surveys via smartphone up to 7 times per day over 8 days, excluding time at school. At each prompt, mothers and children reported on their current NA, PA, and ability to cope with stress and foods consumed in the past 2 hours. RESULTS. Mothers’ momentary ability to cope with stress predicted their own and their child’s pastries/sweets intake and their own fries/chips intake, and children’s momentary ability to cope with stress predicted their own pastries/sweets intake. Mothers and children who reported higher NA on average consumed more pastries/sweets, and children with higher NA on average consumed more fast food. Finally, mothers’ momentary PA predicted their own fruit/vegetable consumption. CONCLUSIONS. Findings provided evidence that the affect and ability to cope with stress of children and mothers predicted subsequent food intake. Given both actor and partner effects, the results show that targeting momentary mothers’ and children’s ability to cope with stress may have the greatest effect on reducing unhealthy food intake.